MODEL INVESTASI FUZZY UNTUK ANALISIS KELAYAKAN FINANSIAL USAHA DIVERSIFIKASI INDUSTRI BERBASIS TEBU - Martini, Sri; Sukardi, Sukardi; Marimin, Marimin; Ismaya, Andes (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 10, No. 2 Juli 2010, 2019)
Financial analysis is required to prevent the failure of a project when it is implemented. The obstacles and risks of the Prolect implementation that might arise should be minimized. The analysis is complex due to uncertain future situation. Fazzy approach is one of the methods to examine and handle this uncertainty. This research is aimed to study finzy financial feasibility indicators, to arrange fuzzy fnancial feasibility model, and to apply this model to bioethanol industry as a derivate of sugar cane product. Feasibility indicators of fazzy rnvestment model studied included NPV Fuzzy, IRR Fuzzy, and B/C Ratio Fuzzy. Raw materials cost, selling price, and interest rate made as fuzzy variables with Triangular Fuzzy Number (ffN) representation. Model feasibility information was categorized into four categories; unfeasible, fairly feasible, feasiSle, and very feasible. Model validation was conducted by comparing rhe fuzzy method output with conventional method. Model verffication on bioethanol industry using fuzzy method showed this industry was feasible to be developed based on assumption of 10 years project periods, with Rp 18.910.000.000 NPV; L.46 B/C ratio; and 253o/o IRR. Calculation using fuzzy method gave different results from conventional method calculation, however it showed on the same trend.